2020
DOI: 10.1111/padr.12313
|View full text |Cite
|
Sign up to set email alerts
|

Childbearing in Italy and Spain: Postponement Narratives

Abstract: Italy and Spain are extreme cases of low fertility linked to postponement of childbearing. Demographers continue to debate causes of postponement. This qualitative study was designed to contribute, by purposively selecting Italian and Spanish women in different socio‐economic circumstances who are partnered, childless and aged 30 to 35. Most want children but “not now” or are deferring the decision whether to have children. Their different circumstances inflect explanations of postponement in a language of cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 40 publications
2
34
0
4
Order By: Relevance
“…Ante el número relativamente limitado de estudios que han abordado aspectos relacionados con las intenciones reproductivas -fundamentalmente, las referentes al aplazamiento-, desde una perspectiva micro para el caso español (Sampedro et al, 2002;Delgado et al, 2009;Alvarez, 2018;Bueno y Brinton, 2019;Lebano y Jamieson, 2020), y, hasta donde sabemos, ante la ausencia total de estudios que lo hayan hecho siguiendo el modelo teórico TPB, esta investigación busca efectuar una aportación científica y social relevante de cara a comprender las percepciones y las valoraciones que estarían configurando el aplazamiento de la tenencia de los hijos.…”
Section: Marco Teóricounclassified
See 2 more Smart Citations
“…Ante el número relativamente limitado de estudios que han abordado aspectos relacionados con las intenciones reproductivas -fundamentalmente, las referentes al aplazamiento-, desde una perspectiva micro para el caso español (Sampedro et al, 2002;Delgado et al, 2009;Alvarez, 2018;Bueno y Brinton, 2019;Lebano y Jamieson, 2020), y, hasta donde sabemos, ante la ausencia total de estudios que lo hayan hecho siguiendo el modelo teórico TPB, esta investigación busca efectuar una aportación científica y social relevante de cara a comprender las percepciones y las valoraciones que estarían configurando el aplazamiento de la tenencia de los hijos.…”
Section: Marco Teóricounclassified
“…Para responder a las preguntas de investigación formuladas -de carácter explicativo y no meramente descriptivo-, se ha optado por una aproximación metodológica de carácter cualitativo, en línea con investigaciones recientes que han abordado aspectos relacionados con la fecundidad y las intenciones reproductivas (Bueno y Brinton, 2019;Lebano y Jamieson, 2020). Aunque los resultados de investigaciones de carácter cualitativo no pueden ser generalizados, su uso permite analizar cuestiones o comportamientos complejos -como el que aquí se aborda-mediante la obtención de un material rico y detallado (Valles Martínez, 2009).…”
Section: Diseño Metodológicounclassified
See 1 more Smart Citation
“…Previous research has identified several central reasons for childbearing postponement including effective contraception, increased women's education and labor force participation, changes in partnerships, housing and economic uncertainty, gender inequity, and changes in values and norms regarding parenthood (for a review, see Mills et al, 2011). Both quantitative data and in-depth interviews studies indicate that especially having a permanent job and secure income are currently a crucial prerequisite for having children in high-income societies: people tend to postpone childbearing when they are uncertain about their economic and material security (Brinton et al, 2018;Goldstein et al, 2013;Lebano & Jamieson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other major reasons to postpone childbearing include the idea of "taking time" to enjoy the lifestyle people have at the moment, as well as the idea of "total motherhood" and heavy investment in children, which is hardly compatible with women's career development (Lebano & Jamieson, 2020). Finally, union dissolution or problems in relationship may also be among the leading reasons to postpone or renounce childbearing, given that both marriage rates and proportions of young adults in stable unions have decreased in Finland recently (Jalovaara & Fasang, 2017;Saarela & Skirbekk, 2020).…”
Section: Introductionmentioning
confidence: 99%